Somatic Expression of Herpes Thymidine Kinase in Mice following Injection of a Fusion Gene into Eggs - Brinster, Ralph L. (Cell, 1981)
A plasmid, designated pMK, containing the structural gene for thymidine kinase from herpes simplex virus (HSV) fused to the promoter/regulatory region of the mouse metallothionein-I gene, was injected into the pronucleus of fertilized one-cell mouse eggs; the eggs were subsequently reimplanted into the oviducts of pseudopregnant mice. The first experiment produced 19 offspring, one of which expressed high levels of HSV thymidine kinase activity in the liver and kidney. pMK DNA sequences were detected in equal amounts in several tissues of the expressing mouse as well as in three mice that did not express HSV thymidine kinase activity. In all cases, several copies of the pMK plasmid were tandemly duplicated and integrated into mouse DNA. It appears as though multiple copies of the intact plasmid were fused by homologous recombination either before or after integration at a single site in the mouse genome. The overall efficiency of obtaining somatic expression of thymidine kinase in experiments performed to date is about 10% (4/41), and twice this number have integrated pMK DNA. This procedure not only provides a means of introducing new genes into mice, but it will also be a valuable system for studying tissue-specific regulation of gene expression.